Fluorescence in the Mucus of Anguispira Cumberlandiana (LEA) - H. C. Rawls; R. L. Johnson; R. L. Smith (Hello World!, 1974)
We now wish to report the occurrence of fluorescence in the mucus of Anguispira cumberlandiana (Lea), and to relate the fluorescence to the presence of pseudomonad bacteria in the mucus of members of this species. The research on which this paper is based is part of a continuing study by the senior author, supported by a grant from the CounciI on Faculty Research, Eastern Illinois University.